Personal, biomechanical and psychosocial risk factors for neck disorders in the working population. (19th October 2011) - Le Manac'h, Audrey Petit; Ha, Catherine; Bodin, Julie; Parot-Schinkel, Elsa; Ramond-Roquin, Aline; Leclerc, Annette; Imbernon, Ellen; Roquelaure, Yves
Abstract : Objectives: To assess the prevalence and risk factors for non-specific neck disorder (ND) in a representative French working population characterised by various levels of exposure to work-related constraints. Methods: The study population comprised 3710 workers (2161 men, 1549 women, mean age = 38.7 years) out of 184 600 surveyed by the 83 occupational physicians between 2002 and 2005. ND during the last 12 months and the preceding 7 days were assessed using the Nordic questionnaire. Personal risk factors and work exposure were assessed by a self-administered questionnaire. Associations between ND during the preceding 7 days and personal and occupational factors were analysed using logistic regression modeling. Results: Forty percent of these workers reported ND at least 1 day during the previous 12 months and 19% during the preceding 7 days. Age (OR=1.18–1.94), female gender (OR=1.94 95% CI (1.6 to 2.3)), previous history of upper limb musculoskeletal disorders (OR=1.44 (1.2 to 1.8)) and arthritis (OR=3.30 (2.0 to 5.4)) were associated with ND. Higher risk of ND was observed in case of arm abduction (OR=1.46 (1.2 to 1.7)) and neck flexion (OR=1.41 (1.2 to 1.8)) during at least 2 h per day. High psychological demand at work (OR=1.27 (1.1 to 1.5)) and low supervisor social support (OR=1.42 (1.2 to 1.7)) were associated with ND. Workers whose work pace depended of outside request (OR=1.31 (1.09 to 1.57)) or colleague's work (OR=1.25 (1.03 to 1.51)) were more likely to suffer from ND. Conclusions: The relative importance of individual, biomechanical, organisational and psychosocial risk factors for ND was similar. This study highlighted several work-related risk factors which can potentially be modified.